Tropisetron alleviate early post‐operative pain after gynecological laparoscopy in sevoflurane based general anaesthesia: A randomized, parallel‐group, factorial study. (19th July 2013) - Mei, W.; Li, M.; Yu, Y.; Cheung, C.W.; Cao, F.; Nie, B.; Zhang, Z.; Wang, P.; Tian, Y.
Abstract Background Studies have suggested that 5‐hydroxytryptamine‐3A (5‐HT‐3A) receptor antagonists may have analgesic effects. This randomized, double‐blind, placebo‐controlled, factorial study tested the hypothesis that 5‐HT‐3A receptor antagonist tropisetron attenuates post‐operative pain in women receiving either sevoflurane or propofol based anaesthesia. Methods Two hundred and ninety‐six women undergoing gynaecological laparoscopies were randomly assigned to be anaesthetized with either sevoflurane or propofol. Immediately after the induction of anaesthesia, the anaesthesiologist administered either tropisetron 2 mg or a placebo intravenously. Pain score at rest at 0.5 h post‐operatively reported using a numerical rating scale was the primary outcome measure. The secondary outcome measures included pain score at rest every 2 h within the first 24 h post‐operatively, duration of post‐anaesthesia care unit stay, incidence of post‐operative nausea and vomiting, the incidence of shivering and score of the Quality of Recovery Score 40. Results Compared with placebo, tropisetron produced a statistically significant decrease on pain report within the first 6 h post‐operatively in the sevoflurane‐based anaesthesia group (3 [2, 4] vs. 5 [4, 5], p < 0.001 in 0.5 h; 2 [0, 4] vs. 3 [3, 5], p < 0.001 in 2 h; 2 [0, 3] vs. 3 [1, 4], p = 0.002 in 4 h; 1 [0, 3] vs. 2 [1, 4], p = 0.016 in 6 h), but not in the propofol‐based group. Conclusions A single‐dose intravenous administration of tropisetron after anaesthesia induction is associated with statistically significant decreased early post‐operative pain in patients undergoing gynaecological laparoscopies under sevoflurane based general anaesthesia.